The Feasibility and Reliability of Transient Elastography Using Fibroscan®: A Practice Audit of 2335 Examinations - Jack XQ Pang; Faruq Pradhan; Scott Zimmer; Sophia Niu; Pam Crotty; Jenna Tracey; Christopher Schneider; Steven J Heitman; Gilaad G Kaplan; Mark G Swain; Robert P Myers (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Liver stiffness measurement (LSM) using transient elastography is widely used in the management of patients with chronic liver disease.